Examination of the Deubiquitylation Site Selectivity of USP51 by Using Chemically Synthesized Ubiquitylated Histones. (21st November 2018) - Ai, Huasong; Guo, Yu; Sun, Demeng; Liu, Sanling; Qi, Yunkun; Guo, Jing; Qu, Qian; Gong, Qingyue; Zhao, Suwen; Li, Jiabin; Liu, Lei
Abstract: Histone ubiquitylation and deubiquitylation processes and the mechanisms of their regulation are closely relevant to the field of epigenetics. Recently, the deubiquitylating enzyme USP51 was reported to selectively cleave ubiquitylation on histone H2A at K13 or K15 (i.e., H2AK13Ub and H2AK15Ub), but not at K119 (i.e., H2AK119Ub), in nucleosomes in vivo. To elucidate the mechanism for the selectivity of USP51, we constructed structurally well‐defined in vitro protein systems with a ubiquitin modification at precise sites. A total chemical protein synthesis procedure was developed, wherein hydrazide‐based native chemical ligation was used to efficiently generate five ubiquitylated histones (H2AK13Ub, H2AK15Ub, H2AK119Ub, H2BK34Ub, and H2BK120Ub). These synthetic ubiquitylated histones were assembled into nucleosomes and subjected to in vitro USP51 deubiquitylation assays. Surprisingly, USP51 did not show preference between H2AK13/15Ub and H2AK119Ub, in contrast to previous in vivo observations. Accordingly, an understanding of the selectivity of USP51 may require consideration of other factors, such as alternative pre‐existing histone modifications, competitive reader proteins, or different nucleosome quality among the in vivo extraction nucleosome and the in vitro reconstitution one. Further experiments established that USP51 in vitro could deubiquitylate a nucleosome carrying H2BK120Ub, but not H2BK34Ub. Molecular dynamics simulations suggested that USP51‐catalyzed hydrolysis of ubiquitylated nucleosomes was affected by steric hindrance of the isopeptide bond. Abstract : Nicking nucleosomes : Five ubiquitylated histones are synthesized through chemical total synthesis and reconstituted to nucleosomes. These histones are used to examine the deubiquitylation selectivity of USP51. Results indicate that USP51 cleaves the surface‐ubiquitylated nucleosomes, but is inactive against ubiquitin embedded inside the nucleosome.